Sensitivity and Specificity of the Geriatric Bedside Swallowing Screen (GEBS): A Diagnostic Accuracy Pilot Study / Sensitivität und Spezifität des Geriatric Bedside Swallowing Screen (GEBS): Eine Diagnostische Pilotstudie - Javorszky Susanne Maria; Reiter Raphael; Frank Wilhelm; Iglseder Bernhard (International Journal of Health Professions)
The projected increase in older adults in the EU to 28.5% by 2050 highlights the need for improved geriatric care. Oropharyngeal dysphagia is common in older adults; it is linked to frailty and neurodegenerative diseases, and can cause malnutrition, dehydration, and aspiration pneumonia. Though screening reduces pneumonia cases in stroke patients, it also risks overdiagnosis in geriatric patients due to age-related swallowing changes that are often misinterpreted by existing tools.